Relationship between sleep quality and subjective well-being: resilience as a mediator and belief in a just world as a moderator - Su, Peng; He, Mu (Frontiers in Psychiatry, 2023)
Background/Purpose: Sleep quality significantly impacts subjective well-being, yet its underlying mechanisms remain largely unknown from a scholarly perspective. Existing research has inadequately addressed the relationship between sleep quality and the subjective well-being of College students. This study primarily investigates the influence of sleep quality on the subjective well-being of College students and explores the mediating role of resilience and the moderating role of belief in a just world. Methods: The study sample comprises 3349 enrolled College students. Measures include the Pittsburgh Sleep Quality Index, the Subjective Well-being Scale, resilience scale, and belief in a just world scale. A moderated mediation model is employed to verify the mediating role of resilience and the moderating role of belief in a just world. Results: (1) Sleep quality among College students is significantly positively correlated with resilience, belief in a just world, and subjective well-being. (2) Sleep quality positively predicts subjective well-being among College students. Resilience among College students serves as a mediator between sleep quality and subjective well-being, while belief in a just world moderates the influence of resilience on subjective well-being. Conclusion: The results suggest that sleep quality can directly enhance the subjective well-being of College students and can also indirectly affect it through resilience. Additionally, belief in a just world can enhance the promoting effect of resilience on the subjective well-being of College students. These findings may contribute to understanding the impact of sleep quality on the subjective well-being of College students and its pathways. These research findings can serve as a reference for improving the subjective well-being of College students.